2013
DOI: 10.1177/1087057113498418
|View full text |Cite
|
Sign up to set email alerts
|

Are GPCRs Still a Source of New Targets?

Abstract: G-protein-coupled receptors (GPCRs) still offer enormous scope for new therapeutic targets. Currently marketed agents are dominated by those with activity at aminergic receptors and yet they account for only ~10% of the family. Progress up until now with other subfamilies, notably orphans, Family A/peptide, Family A/lipid, Family B, Family C, and Family F, has been, at best, patchy. This may be attributable to the heterogeneous nature of GPCRs, their endogenous ligands, and consequently their binding sites. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 210 publications
(334 reference statements)
0
99
0
8
Order By: Relevance
“…The pathogenic triggers at GPCRs vary from hormonal dysregulation, virus infections, mutations, or interactions with autoantibodies. Interestingly, it was recently reported that 365 human GPCRs are potential drug targets (Garland 2013).…”
Section: Gpcr Oligomerization In Endocrine Dysfunctionsmentioning
confidence: 99%
“…The pathogenic triggers at GPCRs vary from hormonal dysregulation, virus infections, mutations, or interactions with autoantibodies. Interestingly, it was recently reported that 365 human GPCRs are potential drug targets (Garland 2013).…”
Section: Gpcr Oligomerization In Endocrine Dysfunctionsmentioning
confidence: 99%
“…1A). 1,2 Since GPCRs comprise one of the largest gene families and ~26% of marketed drugs work by modulating GPCR activation, 3,4 quantification of intracellular cAMP levels remains an important methodology in molecular pharmacological studies of GPCRs. In recent years, biosensors that monitor intracellular cAMP levels have been developed, and the ongoing improvement of these assays provides several opportunities compared with previously employed assays, 5 including the possibility to continuously measure the intracellular cAMP levels in real time.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important insight as GPCRs are attractive targets for drug development because of their role in cell-signaling cascades. 85 However, comparatively little is known about the structural changes associated with agonist or antagonist binding, as of the GPCRs, only rhodopsin has been crystallized in the multiple conformations required to understand the complex structural processes associated with ligand binding. 84 Alongside acting as structural chaperones, the use of antibodies as crystallization aids has been extended to provide vital mechanistic understanding in addition to structural information.…”
Section: Antibody Tools In Structural Studiesmentioning
confidence: 99%